Cyclic cohesive zone modeling for fatigue prediction of concrete-concrete interface in CRTS III slab ballastless track: Theory, algorithm, validation, and application - Yan, Daobin; Shi, Zixuan; Xu, Yude (Engineering structures, 2025)
This paper presents a cyclic cohesive zone model (CCZM) for predicting the interfacial fatigue of concrete-concrete composites in the CRTS III slab ballastless track subjected to high-cycle fatigue loading. The mathematical formulation of the CCZM is detailed, in which the static and the fatigue damage variables representing the interfacial fatigue evolution are derived based on a mixed-mode bilinear cohesive zone model. The numerical algorithm of the CCZM, combined with a valid cycle jump strategy, is programmed in Fortran as a user-defined material subroutine in Abaqus. The predictive capacity of the CCZM under Mode I, Mode II, and Mode I/II loading conditions is validated against interfacial fatigue benchmarks, including the double-cantilever beam (DCB), end-notched flexure (ENF), and single-leg bending (SLB) tests. Furthermore, the CCZM is applied in a finite element (FE) analysis of the interfacial fatigue at the concrete-concrete interface between the track-slab and self-compacting concrete layer in the CRTS III slab ballastless track under cyclic temperature gradient loading, and the results show that the interfacial fatigue may reach level-I and level-II damage within 11 and 15 years, respectively, indicating a potential need for debonding maintenance. •The CCZM is proposed with newly developed static and fatigue damage variables.•The CCZM is implemented by a numerical algorithm through UMAT subroutine.•The CCZM is validated to capture both single- and mixed-mode fatigue behaviors.•Interfacial fatigue may reach damage limit and require maintenance within 15 years.